Footprints in Paradise Ethnography of Ecotourism, Local Knowledge and Nature Therapies in Okinawa - Murray, Andrea (New Directions in Anthropology, 2017)
In Okinawa, the southernmost prefecture of Japan, "ecotourism" promises to provide employment for a dwindling population of rural youth while preserving the natural environment and bolstering regional pride. Footprints in Paradise centers on how Okinawans' sense of place is transforming rapidly, along with language, landscapes, cultural traditions, and wildlife: from marginalized and exoticized island phenomena into global heritage resources worth cherishing by insiders and outsiders. Footprints in Paradise is intended for readers interested in the anthropology of US-Japan-Okinawa relations, tourism and island environments, the politics of ecological sustainability, and the shifting ethics of human-animal relationships in the early twenty-first century.